Kawasaki Disease and the Use of the Rotavirus Vaccine in Children: A Systematic Review and Meta-Analysis - Natália Gibim Mellone; Marcus Tolentino Silva; Mariana Del Grossi Paglia; Luciane Cruz Lopes; Sílvio Barberato-Filho; Fernando de Sá Del Fiol; Cristiane de Cássia Bergamaschi (Frontiers Media S.A., 2019)
Background: The vaccine against the rotavirus is an effective measure in reducing hospitalizations and mortality caused by the virus. However, its use can result in serious adverse effects. The available evidence on Kawasaki disease has not yet been reported in the literature. This study investigated the risk of developing Kawasaki disease with the use of rotavirus vaccines in children.Methods: This is a systematic review of data collected from studies retrieved on the following databases: Cochrane, MEDLINE, Embase, CINAHL, Scopus, Web of Science, HealthSTAR, Lilacs, Clinical trial.gov, and International Clinical Trials Registry Platform, up to the 15th of August 2018, with no restrictions on language or date of publication. The outcomes measured were incidence of Kawasaki disease, risk of developing the disease, and rate of discontinuation of the vaccination schedule. Four reviewers independently selected the studies, performed data extraction, and assessed the quality of evidence. A meta-analysis of random effects was performed.Results: A total of 13 publications were included, with a population of 164,434 children included in the meta-analysis. The incidence of Kawasaki disease (24 cases per 100,000, 95% CI = 11.98-48.26) in the vaccinated children was low. No difference between the vaccines was found in the prevalence rate of adverse effects (RR = 1.55, 95% CI = 0.41-5.93). Use of the vaccines was not associated with risk of developing Kawasaki disease (low-quality evidence). None of the studies reported the rate of discontinuation of the vaccination schedule.Conclusions: The vaccines were associated with a low incidence of developing Kawasaki disease, showing no association with this serious adverse effect.